The application of PPE at the Juanda meteorological station (BMKG) - Fatoni, Arrizal R.; Bahtiar, Ahmad; Faridatussafura, Nurzaka; Hermanto, Ady; Aulady, M. Ferdaus N. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The application of Personal Protective Equipment (PPE) at the Meteorology, Climatology, and Geophysics Agency (BMKG) is an important step in maintaining employees’ safety and health in their work environment. Even though BMKG is not involved in heavy industrial activities, there are still potential hazards and risks that need to be addressed in carrying out meteorological, climatological, and geophysical tasks. This study aims to describe the importance of implementing PPE in the BMKG environment, especially the Aviation Meteorological Station, where we took a case study at the Juanda Meteorological Station. First, we identify potential hazards that may be faced by BMKG employees, such as radiation risk, potential for hazardous gas explosions or fires, extreme weather conditions, and risks of physical injury. In the face of these risks, the use of proper PPE can help protect employees from hazardous exposures, and gas explosions and prevent injury. Next, we discuss the factors that need to be considered in implementing PPE at the BMKG. This includes a comprehensive risk assessment, identification of appropriate PPE for specific hazards, training of employees on the use and care of PPE, and regular monitoring and maintenance of the PPE used. Therefore, by implementing the Occupational Health and Safety Management System, in this case, the application of PPE, BMKG can ensure that employees have a safe and healthy work environment, reduce the risk of work accidents, and comply with applicable regulations and standards related to work safety.